THE EFFECTS OF HUMAN ACTIVITY ON SUMMER HABITAT USE BY MOOSE - Lykkja, Odd N; Solberg, Erling J; Herfindal, Ivar; Wright, Jonathan; Rolandsen, Christer M; Hanssen, Martin G (Lakehead University, 2009)
Non-fatal disturbance by humans can be analogous to predation risk because animal response to both directly reduces time available for other fitness-increasing activities such as foraging, maternal care, and reproductive behaviour. We studied the effects of human disturbance on moose (Alces alces) by examining hourly locations and movement patterns of 41 GPS-marked moose relative to human activity in central Norway during summer 2006. Our results indicated that moose moved further from inhabited houses and to areas of lower housing density in periods of high human activity as compared to periods of low human activity, and that this behavioural response was closely related to the level of human activity in the area used by moose. We also detected significant differences between responses of males and females with calves; males were more willing to use areas near houses and with higher housing density during periods of low human activity. This differential response was likely due to the higher perceived risks of foraging associated with maternal protection of non-independent offspring. Our study supports the idea that indirect cost associated with human disturbance is analogous to the influence of perceived predation risk on animals. We suggest that such indirect effects on moose should be accounted for when planning human construction and activity in prime moose habitat.